TURNOVER AND POLITICISATION OF SENIOR CAREER CIVIL SERVANTS IN LITHUANIAN MINISTRIES IN 2001–2015 - Bacevičiūtė, Aušra (Politologija, 2016)
In this article the results of the research on the turnover and politicization of senior career civil servants (in particular, secretaries, state secretaries and chancellors) in Lithuanian ministries in the period of 2001–2015 are provided.The above-mentioned research revealed that over the analysed period the average extent of politicization of senior career civil servants in the ministries amounted to 39%, while the total share of politicized servants varied between 25% and 45%. It exceeds the politicisation of the management in the Lithuanian government agencies and agencies under the ministries (19%) and state-owned enterprises (36%), however, lags behind that of managers in Lithuania’s educational institutions and personal health care organisations (43% and 53%, respectively).The highest politicisation was observed in the ministries of the interior, transport and communications, and agriculture, while the lowest – in the ministries of finance and justice. Evidence indicates the existence of statistically significant relationship between the amount of state budget allocations for institutions and agencies in the minister’s field of activity, and the degree of politicisation of senior career civil service in the respective ministries. It confirms the notion that public sector organisations rich in financial resources are the most appealing targets for political parties seeking to politicize.The analysis has revealed that demand-side factors, such as the scale of alteration of ruling majorities or alteration of parties holding minister portfolio, are insufficient to explain the turnover and politicisation of ministerial senior career civil servants. In some cases, politically motivated appointments and dismissals of these servants were made regardless of alterations of parties holding minister portfolio or even person serving as minister. Thus, supply-side factors, namely the existence of suitable partisan candidates to fill high-ranking positions in the ministries and opportunities for politicisation, have higher explanatory power.Furthermore, the research revealed the existence of positive relationship between party entrenchment in power and politizication of ministerial senior career civil servants. Parties having relatively more governing experience (the Lithuanian Social Democratic Party and, to a lesser extent, the Liberal and Centre Union and the Homeland Union-Lithuanian Christian Democrats) were more capable of offering suitable partisan candidates for ministerial appointments, thus, politicized relatively more. On the other hand, the size of a party, as such, does not influence its abilities to politicize due to high requirements for candidates to fill high-ranking ministerial positions. Yet, the largest parties also happen to have more governing experience. As a result, they not only had higher capacities to politicize but could successfully take advantage of them, as well.In addition, the substantial difference in politicisation strategies of ideologically opposite political parties was observed. Left parties politicized more while appointing civil servants, right parties – while dismissing them. With an aim to create favourable conditions for politicisation, parties on both sides of political spectrum carried out ministerial structural reforms. However, opportunities provided by the latter were exploited differently by ideologically opposite parties. With the reform of 2002, left-wing governing parties caused structural de-politicisation but took advantage of new appointments to de facto politicize. Completely different situation was observed with regard to the reform of 2009 carried out by right-wing governing parties. The latter conditioned structural politicisation but rarely de facto politicized.Following the reform of 2002, the level of de facto politicisation in ministerial senior career civil service increased, maintaining relatively stable during 2003–2008. Only after the reform of 2009 a decrease in the level of de facto politicisation was observed. This trend did not change even after left-wing parties returned to power in 2012. It is attributable to the changed propotions of career civil servants and those of political (personal) confidence in the ministries. The reform of 2009 resulted in clear quantitative advantage of civil servants of political (personal) confidence against career civil servants. Consequently, the need of the ministers to expand their political teams through de facto politicisation of ministerial career civil servants was reduced. In other words, negative relationship between structural and de facto politicisation was identified.For the future research on politicisation of Lithuanian public sector organisations it is suggested to analyse turnover and politicisation of the same groups of ministerial senior career civil servants in the period not covered by this research (i. e. 1994– 2001), also testing the relationship between structural and de facto politicisation following the ministerial structural reforms of 1996 and 1998.